Biochemical characterization and bacterial diversity of Agrocybe aegerita during postharvest storage - Yang, Cairong; Yang, Jiezhi; Zhou, Yueju; Ou, Yi; Wang, ZhiMeng; Qi, Weiliang; Huang, Renwei; Chai, Songyue; Yang, Hongling; Zhou, Yongfang; Liu, Songqing (Frontiers in Microbiology, 2025)
Agrocybe aegerita, as an edible delicious mushroom, the storage time and quality affect its economic value and industrial development. In the present study, A. aegerita was sealed and packaged in PE self-sealing bags and stored at a storage temperature of 4°C, 90% humidity. The physiological and biochemical indexes of A. aegerita were measured and the bacterial community on the surface of fruit was determined. Soluble protein rapidly decreased in the first 5 days and then stabilized. Superoxide anions and malondialdehyde, showed dynamic fluctuations. Antioxidant enzymes SOD and CAT exhibited variable activities, while POD remained stable. The activity of polyphenol oxidase ascended, while the total phenolic content initially dropped and subsequently registered a marginal increase. In tandem, the ascorbic acid (VC) content underwent a persistent decrease. Cell wall related enzyme displayed distinct temporal activity patterns. Analysis of bacterial diversity showed that Proteobacteria was the dominant phylum and the genus Serratia was the dominant bacterial genus in the storage process of A. aegerita. Alpha diversity analysis showed that with the extension of storage time, the bacterial diversity on the surface of the A. aegerita body gradually decreased. Correlation Network Analysis showed that genera Serratia, Bacteroides, and Sphingomonas were the most closely related bacterial genera to other bacteria, occupying a dominant position in the entire bacterial community. WGCNA showed that Altererythrobacter and Brevibacilluswere might improve the storage quality of A. aegerita. WGCNA also showed that Aeromonas hydrophila and Acinetobacter venetianus might disrupt the cell wall structure of A. aegerita. This study shed light on the understanding of the physiological indicators changes and bacterial community diversity on the surface of A. aegerita fruit during storage. It also provided analysis of the correlation between physiological indicator changes and bacterial community diversity on the surface of A. aegerita fruit, which could provide some support for scientific storage of A. aegerita.